ANALISIS PEMASARAN SALAK PONDOH (Salacca Edulis) DI KECAMATAN GIRIMULYO KABUPATEN KULON PROGO - Andre Priyanto; Susi Widiatmi (JURNAL ILMIAH AGRITAS, 2018)
This research aims to know the factors that affect analysis of marketing efficiency and margin of â€œSalak Pondohâ€ in Girimulyo district, Kulon Progo regency. The basic method of research used in this research is a method of observation and measurement by conducting the interview directly to respondents using quisioner and then collect and collate the data, as well as analysis and explaination. The method of determining the location is done deliberately (purporsive) with the consideration that the selected area is one of the centers of production of â€œSalak Pondohâ€ in Girimulyo district, Kulon Progo regency whereas the determination of a sample of farmers and merchants to use the snowball method. The research results showed that the factors that affect is the present price of the marketing margins of manufacturers, marketing costs and the number of institutions simultaneously real affect against the marketing margin of â€œSalak Pondohâ€. Whereas with the present prices are individually tested the manufacturer is not significantly affect. The efficiency of the marketing channel that is in the Sub-District of Girimulyo showed that all of the channel marketing is already efficient.